Pattern of Postoperative Mortality After Esophageal Cancer Resection According to Center Volume - Markar, Sheraz (2015)
Background High center procedural volume has been shown to reduce postoperative mortality (POM); however, the cause of POM has been poorly studied previously. The aim of this study was to define the pattern of POM and major morbidity in relation to center procedural volume. Methods Data from 2,944 consecutive adult patients undergoing esophagectomy for esophageal cancer in 30 centers between 2000 and 2010 were retrospectively collected. Data between patients who suffered 30-day POM were compared with those who did not. Factors associated with POM were identified using binary logistic regression, with propensity matching to compare low- (LV) and high-volume (HV) centers. Results The 30-day and in-hospital POM rates were 5.0 and 7.3 %, respectively. Pulmonary complications were the most common, affecting 38.1 % of patients, followed by surgical site infection (15.5 %), cardiovascular complications (11.2 %), and anastomotic leak (10.2 %). Factors that were independently associated with 30-day POM included American Society of Anesthesiologists grade IV, LV center, anastomotic leak, pulmonary, cardiovascular and neurological complications, and R2 resection margin status. Surgical complications preceded POM in approximately 30 % of patients compared to medically-related causes in 68 %. Propensity-matched analysis demonstrated LV centers were significantly associated with increased 30-day POM, and POM secondary to anastomotic leak, and pulmonary- and cardiac-related causes. Conclusions The results of this large, multicenter study provide further evidence to support the centralization of esophagectomy to HV centers, with a lower rate of morbidity and better infrastructure to deal with complications following major surgery preventing further mortality.